Preliminary observations on the effect of different canopy and soil moisture conditions on the growth of Calamus manan (manau) - Nainggolan, P. H . J . (RIC, 2013)
Preliminary observations during the first year after transplantation to the field showed that seedlings of Calamus manan had better growth rates and lower mortalities when grown under half-canopy shade or under exposure to the morning sun, than when grown in full shade of the forest. This was true irrespective of whether the trials were conducted under wet or dry soil moisture regimes